Effect of magnesium content on the microstructure and dry sliding wear behavior of centrifugally cast functionally graded A356-Mg2Si in situ composites. (27th April 2018) - Ram, Subhash Chandra; Chattopadhyay, K; Chakrabarty, I
Abstract: Functionally graded A356 alloy (Al–7.2Si–0.3Mg) –Mg2 Si in situ composites have been synthesized via centrifugal casting route. Mg2 Si particles tend to migrate towards the core of the tubular product by centrifugal force. The in situ formed Mg2 Si particles in composites are characterized by x-ray diffraction (XRD) analysis, Energy dispersive spectrometry (EDS), Optical, Scanning Electron and Transmission Electron Microscopy. Apart from primary blocky Mg2 Si particles the matrix contains other phases viz. Al-Si eutectic, pseudo-binary Al-Mg2 Si eutectic and Al-Fe-Si intermetallics. Density is found to decrease and %porosity is increased with increase in volume fraction of Mg2 Si. Maximum hardness was observed at the inner core region due to maximum segregation of Mg2 Si particles and gradually decreases towards the outer periphery region. The dry sliding wear was evaluated with varying parameters such as normal loads (N) and sliding distances (m). A substantial increase in wear resistance at the inner core region is observed. From the worn surface characterization, the wear mechanisms have been explained.